An effective Ni/C co-catalyst for promoting photocatalytic hydrogen evolution over TiO2 nanospheres. (September 2022) - Zhao, Xueying; Xie, Wenyu; Shao, Xueqing; Wang, Zhuan; Yang, Bo; Yang, Chao; Wang, Jide; Su, Xintai
Abstract: Ni/C/TiO2 nanocomposites have been prepared by base-catalyzed hydrolysis of tetrabutyl titanate in the Ni/C suspension and subsequent heat treatment at different temperatures. The Ni/C co-catalyst was fabricated by salt-templated pyrolysis of a nickel oleate complex. Phase and morphological analyses revealed that the Ni/C/TiO2 nanocomposites were largely composed of anatase TiO2 nanospheres. Hydrogen evolution measurements showed that the photocatalytic activity of TiO2 nanospheres was improved by the Ni/C co-catalyst under simulated sunlight. The best-performing Ni/C/TiO2 -T700 achieved a H2 evolution rate of 1745.0 μmol h -1 g -1, which was 9-fold as high as pure TiO2 (185.0 μmol h -1 g -1 ). Based on optical, electrochemical, and photo-electrochemical results, the enhanced catalytic activity could be attributed to the Ni/C co-catalyst promoting the photo-generated charge separation and suppressing the electron-hole pair recombination. This work provides an alternative type of Ni-based co-catalyst for enhancing the hydrogen evolution activity of TiO2 -based photocatalysts.